Predictors of Outcome in Adenoid Cystic Carcinoma of Salivary Glands: A Clinicopathologic Study With Correlation Between MYB Fusion and Protein Expression. (October 2017) - Xu, Bin; Drill, Esther; Ho, Allen; Ho, Alan; Dunn, Lara; Prieto-Granada, Carlos Nicolas; Chan, Timothy; Ganly, Ian; Ghossein, Ronald; Katabi, Nora
Abstract : Adenoid cystic carcinoma (ACC) is the second most common salivary gland malignancy and it has a high rate of recurrences and a poor long-term prognosis. Our aim was to assess the prognostic factors in ACC and study MYB -NFIB fusion and MYB protein expression in a large retrospective cohort of 135 patients with a median follow-up of 6.3 years. The 5- and 10-year local recurrence-free survival (RFS) rate of 94% and 78%, 5- and 10-year distant metastasis survival rate of 77% and 58%, and 5- and 10-year RFS of 66% and 44%. The following features were identified as adverse prognostic factors of RFS on univariate analysis: large tumor size, solid growth pattern, increased mitoses, positive margin, American Joint Committee on Cancer clinical staging, high-grade transformation, vascular invasion, nuclear atypia, open chromatin, prominent nucleoli, and tumor necrosis. However, on multivariate analysis, only increased mitoses (≥5/10 high-power fields), any solid growth pattern, and advanced American Joint Committee on Cancer TNM staging were independent adverse predictors for RFS. MYB immunoexpression and MYB-NFIB translocation were common findings in ACC, occurring in 72% and 59% of the tested ACCs, respectively. The sensitivity and specificity of MYB immunohistochemistry in detecting MYB-NFIB fusion was relatively low at 78% sensitivity and 50% specificity. The high prevalence of alterations leading to high expression of the MYB transcription factor family suggests that targeted approaches developed to suppress the expression of these oncogenic transcription factors and/or the transcriptional activity of these proteins would be a rational therapeutic approach to investigate in ACC.